Correlation between the size of the breast lump and axillary lymph node metastasis in patients with carcinoma of breast. (Anwer Khan Modern Medical College Journal, 2020)
Background: Breast cancer is the most frequently diagnosed cancer and the leading cause of cancer death in females, accounting for 23 percent of total cancer cases and 14 percent of cancer deaths.1 The lifetime probability of developing breast cancer is one in six overall (one in eight for invasive disease).2 In Bangladesh breast cancer is the 2nd most common cancer and also 2nd most leading cause of cancer death among the female population after cervical cancer.3 Despite the decreases in incidence rates in North America, breast cancer incidence has been increasing in other parts of the world, such as Asia and Africa. These international differences are thought to be related to societal changes occurring during industrialization.4,5Methods: This was a Prospective Observational cross-sectional studyconducted among the 150 adult patients of breast carcinoma admitted in Department of surgery of Dhaka Medical College & Hospital, Bangabandhu Sheikh Mujib Medical University and Ahsania Mission Cancer & General Hospital during July 2012 to June 2013. After admission in surgery department, diagnosed patients (by ultrasonography and FNAC) with breast cancer were evaluated by history and physical examination, ultrasonography or mammography in a data collection sheet by the study physician.Tumor size was measured by physical examination, ultrasonography or mammography and during histopathological slide preparation. Histopathology of the dissected axillary lymph nodes determined the axillary lymph node status.Case record forms with appropriate questionnaire were filled for all patients.Results: This prospective documented study enrolled 150 cases of diagnosed breast cancer patient. The mean (+SD) age of the patients was 42.16 + 11.18 years with the range from 18 – 65 years. In this study, commonest presentation was painless breast lump in case of 84% patients. Next to it was nipple retraction (40%). Clinically, 52% of study populations were at stage II. Histologically, most of the tumor was at T2 stage (2.1 to 5 cm). Duct cell carcinoma was the predominant histological type (99.33%) and 58% patient had grade II tumors. 66% population showed metastasis of tumor cells in the axillary lymph node(s). Frequency of axillary lymph node metastasis increased as the tumor size increased. We found 33.33% T1 tumors had axillary lymph node metastasis, where as 58.97% T2 tumors and 93.75% T3 tumors showed axillary lymph node metastasis respectively.AKMMC J 2020; 11(2) : 107-112